Identification of Macrofungal Diversity in Limestone Mining Areas - Yudhistian, Yudhistian; Rohmah, Khafidhotur; Suwondo, Prapto; Wulandari, Tabitha Sri Hartati (Universitas Sultan Ageng Tirtayasa, 2024)
This study aimed to identify the diversity of macrofungi in the Paciran limestone mining area. This type of research is quantitative descriptive, identifying and describing the macrofungi diversity level in the Paciran limestone mining area. The method used is observation with data collection using a 1x1 meter plot technique and then continued to count the macrofungal species in the plot and analyze it using the Shannon & Wienner (1963) diversity index equation. In addition, the morphological characteristics of each macrofungi were noted and entered into the observation table. The research results showed that 10 species of macrofungi belonging to two divisions, namely Ascomycota and Basidmycota, were identified, totaling 377 individuals. The Ascomycota division has a low level of diversity with a value of 0.6, while the Basidiomycota division has a medium level of diversity with a value of 1.40. The diversity of macrofungi in the Paciran limestone mining area can be used as a contextual learning resource for lower plant botany to provide insight and increase contextual knowledge related to macrofungi diversity for biology education students.